Clinical comparative analysis of various duodenal diseases in different age groups - Jin Zhao; Xuelian Li; Qi Liu; Linyan Shi; Ling Zhang; Hong Yang; Qianqian Zhang (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study aimed to investigate the differences and relevance of various common duodenal diseases in different parts in the aspects of age, gender, helicobacter pylori (H. pylori) infection, application of nonsteroidal anti-inflammatory drugs (NSAIDs), smoking, or alcohol consumption.Materials and Methods: The medical records of various duodenal diseases were collected and tested for difference using the χ2 test or the Fisher exact probability method.Results: 1) The proportions of duodenal ulcer (DU), inflammation, and duodenal bulb diseases in the adult group (A) (47.98%, 36.70%, and 66.63%) were higher than those in the elderly group (E) (41.38%, 29.83%, and 56.82%), but the proportions of duodenal diverticulum (DD) and tumor diseases in the descending and ascending segments (2.95%, 1.43%, 9.14%, and 0.14%) were lower than those in group E (13.73%, 3.69%, 19.41%, and 0.76%) (p<0.001). 2) The positive rate of H. pylori (63.64%) in the duodenal bulb diseases was higher than that in the bulb-descending segment (53.75%), but the application rate of NSAIDs (16.44%) in the duodenal bulb-descending diseases was lower than that in the descending segment (24.81%) (p<0.001).Conclusion: 1) DU, inflammation, and duodenal bulb diseases are common in adults, but DD and tumor diseases in the descending and ascending segments are more common in the elderly. 2) Compared with the duodenal bulb-descending diseases, the application of NSAIDs has greater impact on the diseases in the descending segment, and the rate of H. pylori infection is higher in duodenal bulb diseases.Cite this article as: Zhao J, Li X, Liu Q, et al. Clinical comparative analysis of various duodenal diseases in different age groups. Turk J Gastroenterol 2020; 31(7): 489-96.